2003
DOI: 10.1002/pmic.200390029
|View full text |Cite
|
Sign up to set email alerts
|

Hyperubiquitination of proteins in dilated cardiomyopathy

Abstract: Protein degradation by the ubiquitin-proteasome pathway plays an important role in a variety of fundamental cellular processes, including cell cycle regulation, transcription, antigen processing and muscle remodelling. Research into disorders associated with the ubiquitin-proteasome system has been mainly in the field of neurodegenerative diseases. It is however becoming increasingly apparent that defects in the system are responsible for a number of non-neurological pathologies. Based on initial observations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(161 citation statements)
references
References 38 publications
5
153
0
3
Order By: Relevance
“…Unlike similar methods, which have been reported in other organisms, our method does not require predeleting the native Ub genes (21) or high expression levels of a recombinant Ub gene (21)(22)(23). Two methods for identifying Ub proteins from human cells were published recently (24,25). In common with our approach, these methods do not require any genetic manipulation of the cells used for protein extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike similar methods, which have been reported in other organisms, our method does not require predeleting the native Ub genes (21) or high expression levels of a recombinant Ub gene (21)(22)(23). Two methods for identifying Ub proteins from human cells were published recently (24,25). In common with our approach, these methods do not require any genetic manipulation of the cells used for protein extraction.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially interesting because Weekes et al have previously reported hyperubiquitination in both dilated cardiomyopathy and ischemia of the heart. 17 Another interesting gene that was differentially regulated by the AT 2 receptor was RGS7. Although there is no direct evidence, it can be speculated that the AT 2 receptor may decrease AT 1 receptormediated increases in calcium mobilization through the regulation of this gene.…”
Section: Discussionmentioning
confidence: 99%
“…A consistent finding among all of the studies is the observation that polyubiquitinated proteins are increased in DCM/failing hearts compared with control hearts (Table 1). This has been measured by quantitative Western blot analysis using antibodies that recognize ubiquitin with densitometric analysis of high molecular weight proteins (9,38,71,96,101). Immunolabeling for ubiquitin in fixed tissue sections has also revealed a greater number and size of ubiquitin-positive deposits in failing myocardium compared with controls (25, 29,38,60,88,101).…”
Section: Ups Function In Human Dcm and Heart Failurementioning
confidence: 99%
“…A functional UPS is critical for normal protein turnover and removes damaged or misfolded proteins in a multistep process (24,39,66,93). Dysfunction of the UPS is rapidly gaining recognition as a potentially important mechanism involved in the pathogenesis of a number of cardiac diseases, including heart failure (38,71,88,93,96,101), cardiomyopathies (12,44,71,78), hypertrophy (18,29,54,72), atrophy (2,72), ischemia-reperfusion (41,67), and atherosclerosis (30), providing a strong rationale for further study of specific mechanisms of proteasome impairment and identification of specific targets for therapy. In vitro and animal models have proven highly valuable in assessing effects of various stressors on the UPS and, in some cases, suggesting a causal link between defective protein clearance and disease phenotypes (14,41,46).…”
Section: Introductionmentioning
confidence: 99%